Enhancing seawater desalination performance using a vortex generator in a modified window air conditioner - Nurkholid, Nurkholid; Mugisidi, Dan; Widodo, Widodo; Heriyani, Oktarina; Sulistiono, Ibnu (Politeknik Negeri Lhokseumawe, 2025)
The growing demand for air conditioning systems has driven research into alternative applications, such as seawater desalination. This study evaluates the performance of a modified window air conditioner (WAC) integrated with a vortex generator for desalination. Experiments were conducted using R410A refrigerant under four conditions: closed container (CC), without vortex (WV), connected vortex (CV), and separated vortex (SV). Seawater was heated via the condenser to 55–60°C, controlled by a thermostat, and data was collected every five minutes over eight hours. The thermodynamic properties of R410A were analyzed using Refprop software to determine refrigeration effect (RE), compression work (CW), and coefficient of performance (COP). Results indicate that the SV configuration achieved the highest evaporation rate (5.01 kg) but led to a lower COP (3.91) due to increased condenser temperature and compressor workload. Conversely, CC yielded the highest COP (5.08) by stabilizing the evaporator air temperature and reducing compressor effort. These findings suggest that vortex generators enhance evaporation rates but reduce system efficiency. Further research is needed to optimize vortex generator configurations to improve desalination efficiency while minimizing COP reduction.